Choosing Non-Vitamin K Antagonist Oral Anticoagulants: Practical Considerations We Need to Know - Amin, Alpesh (Ochsner J, 2016)
BACKGROUND: Warfarin is a well-established agent for use in the prevention of stroke or systemic embolic event (SEE) in patients with nonvalvular atrial fibrillation (NVAF) and for the treatment of venous thromboembolism (VTE). However, management of patients requiring oral anticoagulation with warfarin can be complicated by the need for frequent monitoring, drug-drug and drug-food interactions, and a variable response based on genetic polymorphisms. The non–vitamin K antagonist oral anticoagulants (NOACs) were developed as alternatives to warfarin; they do not require routine monitoring and have predictable pharmacokinetics, fewer drug-drug interactions, and limited drug-food interactions. Four NOACs—dabigatran, rivaroxaban, apixaban, and edoxaban—have received approval from the US Food and Drug Administration for the prevention of stroke or SEE in NVAF and for the treatment of VTE. Selecting the most appropriate agent for each patient should be done in consideration of patient preferences and characteristics, including renal function, bleeding risk, and the need for other medications. METHODS: A search was performed on the terms atrial fibrillation and venous thromboembolism with individual terms dabigatran, apixaban, edoxaban, or rivaroxaban to identify relevant manuscripts; large randomized clinical trials, metaanalyses, and treatment guideline recommendations were given preference. Searches to identify registries, treatment guidelines, and metaanalyses relevant to specific subgroups were also used. RESULTS: NOACs are effective in reducing the risk of stroke or SEE in patients with NVAF and are associated with fewer incidents of intracranial bleeding vs warfarin. CONCLUSION: NOACs provide a convenient and safe alternative to warfarin and may result in improved therapeutic outcomes for patients with NVAF or VTE. The use of NOACs in other indications and patient populations is under investigation, and clinical trials investigating their use in acute coronary syndrome, medically ill patients, percutaneous coronary intervention, cardioversion, catheter ablation, coronary arterial disease, and heart failure have been announced.